MENDORONG KEWIRAUSAHAAN GEN Z DENGAN MENGOPTIMALKAN SOSIAL MEDIA - Subhan, M. Nuruddin; Andhyka, Bintang; Indriati, Petiana; Nugroho, Adi; Nisa, Chaerani; Widyaningsih, Murti; Yustisiana, Riska; Herniansyah, Kurnia; Andres, Shan Nemuel; Ephraim, Nathanel (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2024)
Cultivating an entrepreneurial mindset from a young age might inspire youths to pursue entrepreneurship. Introducing the entrepreneurial spirit is crucial for high school students. You are expected to have a business plan ready to be implemented when you become an undergraduate student. Faculty of Economics and Business at Pancasila University (FEB UP) mandates its academics to engage in community service as part of their responsibilities. One type of service involves fostering an entrepreneurial mindset through social interaction. FEB UP lecturers conduct entrepreneurship outreach lectures to help high school students understand entrepreneurship. The seminar activities indicate a strong interest in the entrepreneurial profession.